2018
DOI: 10.3390/atoms6030049
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sections and Rate Coefficients for Rotational Excitation of HeH+ Molecule by Electron Impact

Abstract: Cross sections for rotational excitation and de-excitation of the HeH+ ion by an electron impact are computed using a theoretical approach that combines the UK R-matrix code and the multi-channel quantum defect theory. The thermally-averaged rate coefficients derived from the obtained cross sections are fitted to an analytical formula valid for a wide range of temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In a previous study [19] (hereafter referred to as paper I), we reported cross sections and rate coefficients for vibrational excitation for transitions between the five lowest vibrational levels. In a further study [20] (hereafter referred to as paper II), we presented similar data for rotational transitions in collisions of 4 HeH + with electrons. In the present study, as a follow-up of papers I and II, we determine cross sections and rate coefficients for vibrational and rotational (de-)excitation for collisions of the four stable HeH + isotopologues with electrons.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study [19] (hereafter referred to as paper I), we reported cross sections and rate coefficients for vibrational excitation for transitions between the five lowest vibrational levels. In a further study [20] (hereafter referred to as paper II), we presented similar data for rotational transitions in collisions of 4 HeH + with electrons. In the present study, as a follow-up of papers I and II, we determine cross sections and rate coefficients for vibrational and rotational (de-)excitation for collisions of the four stable HeH + isotopologues with electrons.…”
Section: Introductionmentioning
confidence: 88%
“…50 100 500 2000 5000 0 1 2 3 4 5 6 7 electrons, for k e (j → j ) we used the approximations given by [29]. Since, the rates of collisional de-excitations by electrons and atomic hydrogen are proportional to their number densities,…”
Section: Heh + Collisional (De)excitation In Dark Agesmentioning
confidence: 99%
“…The population of the rotational levels in the epoch of Dark Ages is defined by collisions with photons of the cosmic microwave background (CMB), free electrons, ions and atoms. Calculations of coefficients for rotational and vibrational excitation/de-excitation rates by electrons are performed by [4,24,29,51]. However, up to date, there are no estimations for HeH + rotational excitation/deexcitation by collisions with atomic hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of the FT approach with multichannel quantum defect theory (MQDT) [6,7] have been previously applied to treat numerous electron-cation collision and molecular photofragmentation systems (see, * roman.curik@jh-inst.cas.cz e.g., Refs. [8][9][10][11][12][13][14][15][16][17]) and still more applications can be found in Rydberg spectroscopy [7]. The cornerstone of these studies is the body-frame quantum defect (or phase shift) µ(R, ) that describes a phase gained by the scattered (or Rydberg) electron inside the molecular core.…”
Section: Introductionmentioning
confidence: 99%